Welding procedures influence analysis on the residual stress distribution and distortion of stiffened panels welded via robotized FCAW. (August 2019) - Rodrigues, Lino A.S.; Loayza L, Cristhian R.; Borges, Diego J.A.; Baia, Paola E.C.; Freitas, Elaine N.; Braga, Eduardo M.
Abstract: Residual stresses and distortions reduce the performance of welded structures. A lot of mechanisms were developed to minimize its consequences. Although, welding sequences (WSQ) effect in the residual stresses, measured by a portable XRD equipment in standard stiffened panels, were not deeply studied so far. In this paper, three sequences significantly changed the residual stresses, which are generated by the arc welding process due to the effect of the temperature, directly affecting the distortions. As a result a simple and inexpensive modification in the WSQ, the longitudinal and transversal compressive residual stresses were reduced by 59% and 86%, respectively. Distortions were also decreased by 68%. A higher welding velocity (100 cm/min) and low heat input (0.64 KJ/mm) were obtained by application of robotized FCAW. The results could prove the viability of using the portable XRD analyses in the shipbuilding industry. Graphical abstract: Image 1 Highlights: FCAW robotized process allowed a low heat input in the stiffened panel. Residual stresses were measured via DRX in a stiffened panel in scale. The best sequence decreased distortions and residual stresses.